Product Quality in Different Markets and Cost Structure - Kiyoshi Matsubara (European Regional Science Association (ERSA), 2011)
This paper analyzes the behavior of monopoly firm serving its products to two countries. The main focus of this paper is on how the product-quality choice in different markets are related with the cost structure of the firm. First, This paper examines the effects of production and R&D costs on the product quality separately, and then discusses the general case where the both costs exists. This paper shows that if only production costs exist, providing different levels of product quality is optimal and that if only R&D costs exist, providing the same level of quality is optimal. About the general case, this paper shows the conditions with which the same-quality strategy is optimal in terms of utility and other parameters. As an application, this paper discusses the firm's decision on entry in a foreign market either by exports or FDI. The result is consistent with observations in emerging economies.
Keywords: 330